2012
DOI: 10.1007/s11064-012-0707-3
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Stress May be Induced by the Elevated Homocysteine in Schizophrenic Patients

Abstract: The mechanisms of oxidative stress in schizophrenic patients are not fully understood. In the present study, we investigated the effect of elevated level of homocysteine (Hcys) on some parameters of oxidative stress, namely thiobarbituric acid reactive substances (TBARS), an index of lipid peroxidation in plasma, the level of carbonyl groups in plasma proteins, as well as the amount of 3-nitrotyrosine in plasma proteins isolated from schizophrenic patients. Patients hospitalised in I and II Psychiatric Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 34 publications
2
47
0
3
Order By: Relevance
“…In agreement with our findings, other authors reported that schizophrenic patients in their study groups also had folate and B12 levels within normal limits [28]. These findings suggest that the patients in our study group were not undernourished.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, other authors reported that schizophrenic patients in their study groups also had folate and B12 levels within normal limits [28]. These findings suggest that the patients in our study group were not undernourished.…”
Section: Discussionsupporting
confidence: 93%
“…Through the clinical studies of hospitalized schizophrenia selected from an average disease duration of 5 years treated with second antipsychotic drugs during therapy, DietrichMuszalska, et al [4] found that carbonyl groups and 3-nitrotyrosine were significantly higher in the experimental group thans the normal control group. Herken, et al [5] and Al-Chalabi, et al [6] found that erythrocyte thiobarbituratic acid reactive substances (TBARS) in chronic schizophrenics treated with stable daily doses of neuroleptics and serum malondiadehyde (MDA) in patients newly diagnosed with schizophrenia were significantly increased, respectively.…”
Section: Elevated Indicator Level Of Oxidative Stress In Schizophreniamentioning
confidence: 99%
“…Through the clinical studies of hospitalized schizophrenia selected from an average disease duration of 5 years treated with second antipsychotic drugs during therapy, DietrichMuszalska, et al [4] found that carbonyl groups and 3-nitrotyrosine were significantly higher in the experimental group thans the normal control group. Herken, et al [5] and Al-Chalabi, et al [6] found that erythrocyte thiobarbituratic acid reactive substances (TBARS) in chronic schizophrenics treated with stable daily doses of neuroleptics and serum malondiadehyde (MDA) in patients newly diagnosed with schizophrenia were significantly increased, respectively.…”
Section: Elevated Indicator Level Of Oxidative Stress In Schizophreniamentioning
confidence: 99%